MODERN REPRESENTATIONS ON THE STRUCTURE AND CONDUCTIVITY OF WATER - Запольський, А. К.; Першина, К. Д.; Герасимчук, А. І.; Каздобін, К. О. (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2013)
Overview of the state-of-art representations of water structure and its electrical conductivity are given from the standpoint of its heterogeneous structure. The water structure is fractal, it has water molecules coupled together in clusters with some variable quantity. Clusters are alternating with voids (holes). Basic structural element of cluster is a tetrahedron. The formation of large clusters, presence of Brownian motion and impact of various physical factors (turbulization of water, the effect of electromagnetic fields, pressure, sound, etc.) lead to the destruction of hydrogen bonds, which explains the small duration of cluster existence (10-13 s); so-called "blinking clusters" are formed which are in continuous spontaneous interaction with other clusters or individual water molecules. In their interactions OH• radicals and H3O+ (H5O2+) can form which lead to the formation of hydrogen peroxide, H2O2, atomic hydrogen, and new clusters. Structure of water can be stabilized by dissolved gases and substances that also interact with clusters and individual water molecules. Consequently, the transfer of electrical charges in water occurs by mixed proton - electron conductivity resulting from spatial charge separation in supramolecular structures. Therefore, the classical fundamentals of electrical conductivity as a consequence of the reorganization of the solvent is realized in water as the formation of distributed charges in the "oxonia (H3O+) or OH- ions - solvated electrons”, and such conductivity coming from the formation of such pairs is the exciton.